Analysis of Soil Fertility in Oil Palm Plantation (Elaeis guineensis Jacq) Smallholder Farmers in East Luwuk District, Banggai Regency: Soil fertility of smallholder oil palm plantation - Jen Achen Amu; Herwin Yatim; Irsan Tatu; Hidayat Arismunandar Katili (CELEBES Agricultural, 2022)
One of the factors that influence the production of oil palm plantations is the condition of the land favorable for their growth and development, especially regarding the physical and chemical properties of the soil and the status of soil fertility. The purpose of this study was to determine soil’s physical and chemical properties, as well as its fertility status on smallholder oil palm plantations. Soil sampling was conducted through a descriptive exploratory survey method, involving six sampling points and representing three oil palm ages (11, 16, and 22 years old). The soil chemical and fertility status were analyzed using the National Criteria of Soil Chemical Properties developed by Soil Research Institute and Five Major Soil Chemical Properties approach developed by Soil Research Center. All observed soil exhibited clay textures and varying soil color matrix. The soil had neutral acidity, medium to high base saturation/BS and cation exchange capacity/CEC, moderate P2O5, as well as low organic C and K2O. Soil fertility status on the entire sites were classified as low, which primarily caused by low soil organic C and K contents. In order to improve soil condition favorably for oil palm growth and development, further studies must be conducted using more direct approach, relating the oil palm requirement with current state of soil and land conditions.